Maximizing Energy Storage of Flexible Aqueous Batteries through Decoupling Charge Carriers. Issue 14 (19th February 2021) - Dai, Chunlong; Jin, Xuting; Ma, Hongyun; Hu, Linyu; Sun, Guoqiang; Chen, Hao; Yang, Qiuju; Xu, Maowen; Liu, Qianwen; Xiao, Yukun; Zhang, Xinqun; Yang, Hongsheng; et al.
Abstract: Flexible aqueous rechargeable batteries that integrate excellent mechanical flexibility and reliable safety hold a great promise for next‐generation wearable electronics. Unfortunately, currently available options are unsatisfactory due to their low specific capacity, limited energy density, and unstable voltage output. Herein, to overcome these challenges, high theoretical specific capacity zinc and sulfur as the anode and cathode are selected, respectively. Furthermore, a strategy is proposed, that decoupling charge carriers in anolyte and catholyte to simultaneously endow the zinc anode and sulfur cathode with optimal redox chemistry, maximizes the energy storage of flexible aqueous batteries. The new zinc–sulfur hybrid battery possesses merits of ultrahigh theoretical specific capacity (3350 mAh gS −1 ) and volumetric energy density (3868 Wh L −1 ), low cost, ecofriendliness, and ease of fabrication and is a promising next‐generation aqueous energy storage system. The fabricated flexible aqueous zinc–sulfur hybrid battery delivers a stable output voltage (release 92% of its full capacity within a small voltage drop of 0.15 V) and an ultrahigh reversible capacity of 2063 mAh gS −1 at 100 mA gS −1, thus setting a new benchmark for flexible aqueous batteries and is promising to play a part in future flexible electronics. Abstract : A decoupling‐charge carrier strategy is proposed to develop a new flexible aqueous Zn–S hybrid battery, which simultaneously endows the zinc anode and sulfur cathode with optimal redox chemistry, thus maximizing energy storage. The Zn–S hybrid battery is a promising next‐generation aqueous energy storage system. It represents an advancement in the field of safe flexible energy storage.